CLINICAL PROFILE OF CHILDREN UNDERGOING HEMATOPOIETIC STEM CELL TRANSPLANTATION - Jéssica Alline Pereira Rodrigues; Maria Ribeiro Lacerda; Ingrid Meireles Gomes; Márcio Roberto Paes; Renata Perfeito Ribeiro; Carmem Maria Sales Bonfim (Universidade Federal do Paraná, 2019)
Objective: to identify the clinical profile of children in the hematopoietic stem cell post-transplant period.Method: quantitative, cross-sectional, retrospective study, performed in a transplantation service of the South of Brazil, with data from the medical records of children less than 12 years of age, who had undergone transplantation. Measures of central tendency, dispersion and frequency were used for the analysis and the chi-squared and Fisher's tests to associate variables. Results: the mean age was 6.2 years, males, with 92 (66.7%), the diagnosis of Fanconi anemia, with 42 (30.4%), and unrelated allogeneic transplantation, with 71 (51.4%), were predominant. Hospital discharge occurred within 30 days after transplantation for 85 (61.6%) patients and 48 (34.8%) were readmitted. Catheter failures occurred in 11 children (8.0%) and the main outpatient clinical intercurrences were pain, cough, runny nose and fever. Viral infection was associated with the unrelated transplant and graft-versus-host disease.Conclusion: the profile identified corroborates the care planning for this population, contributing to the nursing practice.